Claim your money / Shafinar Ismail … [et al.] - Ismail, Shafinar; Hashim, Nurhaslinda; Mohamed, Nor Aizan; Mohd Husin, Muhammad Nizar; Mohd Jefri, Muhammad Syukri; Shaharuddin, Fatin Nabila; Abdul Malek, Farissa Alyna (Division of Research and Industry Linkages, 2017)
Unclaimed money is accounts in financial institutions or companies that have had no activity generated or contact with the owner for a year or longer and mainly made up of inactive bank accounts, unclaimed fixed deposits that have expired, insurance pay-outs and interests. It is being held in trust by the Registrar of Unclaimed Moneys in the Accountant-General’s Department. The unclaimed money problem in this country is getting out of hand and all that missing stuff is starting to pile up. A staggering RM 5.779 billion remains unclaimed by Malaysians, all the way from 1977 up to June 30, 2017 (New Straits Times, 2017). The total unaudited amount stands at RM 8.8 billion. So far, only RM 1.579 billion has been returned. (Deputy Finance Minister, Dato’ Othman Aziz, 2017). This will help to reduce the number of unsolved cases in unclaimed monies, avoid a lengthy and costly process of unclaimed monies, offers automated convenience checks for users, and allow users to manage your financial affairs by following specific written instructions. This application is created for self-managing unclaimed money that can be easily accessed by all. These unclaimed monies must be claimed in order to increase the value of ringgit in Malaysia. When citizens use the money to make day to day transactions, thus the purchasing power in Malaysia will also increase. This application is aimed to be sold to the Accountant General's Department o f Malaysia, collaborating with the financial Institutions and non-Bank Financial Institutions.